Identifying Interesting Sceneries and Objects in A Tropic Forest Through Visitors Employed Photography - Akhmad Arifin Hadi; Andi Gunawan; Tsuyoshi Honjo; Katsunori Furuya (School of Postgraduate Studies, Diponegoro Univer, 2024)
Tropical Forest is a unique forest landscape character composed of vegetation with various altitude strata combined with other biotic and abiotic landscape elements. The combination of landscape objects produces a landscape character that is visually attractive to visitors. There are few references to forest sceneries and objects of interest to forest visitors, even though this information is important for forest tourism. This study identified tropical forest sceneries and objects of interest to forest visitors through photographs taken by visitors. The method used is Visitors' Employed Photography (VEP) combined with GPS tracking and artificial intelligence Google Clouds Vision API. In this VEP method, we invited 41 respondents to walk in the